A streamlined approach to online linguistic surveys. - Erlewine, Michael; Kotek, Hadas (Natural Language & Linguistic Theory, 2016)
More and more researchers in linguistics use large-scale experiments to test hypotheses about the data they research, in addition to more traditional informant work. In this paper we describe a new set of free, open-source tools that allow linguists to post studies online, turktools. These tools allow for the creation of a wide range of linguistic tasks, including grammaticality surveys, sentence completion tasks, and picture-matching tasks, allowing for easily implemented large-scale linguistic studies. Our tools further help streamline the design of such experiments and assist in the extraction and analysis of the resulting data. Surveys created using the tools described in this paper can be posted on Amazon's Mechanical Turk service, a popular crowdsourcing platform that mediates between 'Requesters' who can post surveys online and 'Workers' who complete them. This allows many linguistic surveys to be completed within hours or days and at relatively low costs. Alternatively, researchers can host these randomized experiments on their own servers using a supplied server-side component.